Specification for robotic arc welding safety (American Welding Society, 2018)
This standard establishes safety requirements with respect to the design, manufacture, maintenance, and operation of arc welding robot systems and ancillary equipment. It also helps to identify and minimize hazards involved in maintaining, operating, integrating, and setting up of arc welding robot systems.
"Approved by American National Standards Institute, February 16th, 2018."
"AWS D16.1M/D16.1:2018."
Keywords: Electric welding -- Automation -- Standards.; Welding -- Safety measures.; elektronické knihy; electronic books